2009
DOI: 10.1093/nar/gkp178
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism of DNA-dependent ATP hydrolysis mediated by DNA-dependent ATPase A, a member of the SWI2/SNF2 protein family

Abstract: The active DNA-dependent ATPase A domain (ADAAD), a member of the SWI2/SNF2 family, has been shown to bind DNA in a structure-specific manner, recognizing DNA molecules possessing double-stranded to single-stranded transition regions leading to ATP hydrolysis. Extending these studies we have delineated the structural requirements of the DNA effector for ADAAD and have shown that the single-stranded and double-stranded regions both contribute to binding affinity while the double-stranded region additionally pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…These derivatives, ADAADiK and ADAADiN respectively, were purified and titrated with protein while monitoring the quenching of the intrinsic tryptophan fluorescence. Analysis of the data demonstrated that both ADAADiN and ADAADiK bind to ADAAD in the absence of either ATP or stem-loop DNA (slDNA), a well-characterized DNA effector of ADAAD [13]. The data fit well to a one-site saturation model, suggesting that the ADAADi-ADAAD interaction was predominantly via a single site, and the K d was calculated to be 35.8±5.0 nM for ADAADiN and 21.9±4.2 nM for ADAADiK (Figure S1A and S1B; Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These derivatives, ADAADiK and ADAADiN respectively, were purified and titrated with protein while monitoring the quenching of the intrinsic tryptophan fluorescence. Analysis of the data demonstrated that both ADAADiN and ADAADiK bind to ADAAD in the absence of either ATP or stem-loop DNA (slDNA), a well-characterized DNA effector of ADAAD [13]. The data fit well to a one-site saturation model, suggesting that the ADAADi-ADAAD interaction was predominantly via a single site, and the K d was calculated to be 35.8±5.0 nM for ADAADiN and 21.9±4.2 nM for ADAADiK (Figure S1A and S1B; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…His-ADAAD, used for binding studies, was purified as described previously [13]. For mapping and CD studies, ADAAD as well as deletion constructs were expressed as GST-fusion protein in BL21 (DE3) cells and purified as described previously [14].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations